Acromioclavicular joint disruptions: A comparison of two surgical approaches 'hook' and 'rope'. (18th January 2018) - Athar, MS; Ashwood, Neil; Arealis, Georgios; Hamlet, Mark; Salt, Emma
Introduction: Acromioclavicular joint injuries are common shoulder girdle injuries most commonly resulting from a direct blow to the acromion with the arm adducted. Type-I or type-II acromioclavicular joint injuries can be managed with sling immobilization, early shoulder motion, and physiotherapy. The management of type-III injuries remains controversial and is individualized. Type IV and V injuries should be treated surgically. A myriad of surgical techniques for the management of acromioclavicular joint injuries have been reported. Methods: We present a comparative study of 76 patients treated with two most common modalities of treatment for AC joint disruption and that is Hook plate stabilisation (n=52) or arthroscopically assisted tight rope stabilisation (n=24). The primary objective was to establish whether hook plate stabilization was superior compared to arthroscopic tight rope fixation in reducing pain and increasing function in the short-term and long-term for patients with AC joint disruptions III-IV. We also wanted to assess how quickly patients returned to their work/job. It was a prospective study, we included all the patients operated between 2008 and 2015 for AC joint disruption by the two shoulder surgeons of our department. All patients followed a strict physiotherapy protocol and were assessed at 6 weeks, 3 months and 12 months. We used the Harm and cost criteria of assessment and the patient specific functional outcome scores. Results: Both modalities of treatment have high patient satisfaction rate, return to work is faster in tight rope group but after a year both group of patients returned to their premorbid state. Removal of hook plate is not mandatory and lysis of acromion is rare (1% in our series). Conclusion: Despite the fact that both methods yielded similar results and have statistically similar number of complications, the type of postoperative complications was different between groups. The plate group had more postoperative pain and worse function but both aspects improved after plate removal. The rope group had more complex complications including deep infection and recurrence of deformity and fracture. These differences should be taken into consideration when consenting the patient regarding possible treatment.